2013
DOI: 10.1515/bmt-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic particle imaging scanner with 10-kHz drive-field frequency

Abstract: Magnetic particle imaging (MPI) can be used as a fast diagnostic method for obtaining three-dimensional images from inside the body of small animals by the use of functionalized magnetic nanoparticles as tracer. Here, we present our scanner setup working at 10-kHz drive-field frequency to sample a field of view of 22 × 22 × 15 mm(3) with up to 32 volume images per second. A resolution of about 1 × 2 × 1 mm(3) is achieved with iron oxide nanoparticles (Resovist). We discuss the properties of the complete system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Magnetic particle imaging (MPI) directly measures the spatial distribution of MNP concentration using the magnetic response of the MNPs to drive and selection magnetic fields [24][25][26][27]. Furthermore, multi-color MPI, in principle, allows the imaging of biomolecules in addition to concentration via the measurements of nanoparticle relaxation [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic particle imaging (MPI) directly measures the spatial distribution of MNP concentration using the magnetic response of the MNPs to drive and selection magnetic fields [24][25][26][27]. Furthermore, multi-color MPI, in principle, allows the imaging of biomolecules in addition to concentration via the measurements of nanoparticle relaxation [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature have shown that the drive waveform affects MPI spatial resolution 29 30 31 32 33 34 35 . Unfortunately, current MPI hardware is limited to only sinusoids at a few discrete frequencies 2 3 26 27 28 36 37 38 39 40 41 42 . Multiple simultaneous frequencies (Philips-Bruker 3D Fast MPI demonstrator scanner 15 ) is limited to a narrow range (24.51 kHz, 25.25 kHz, and 26.04 kHz).…”
mentioning
confidence: 99%
“…Regarding the magnetic properties of the five individual synthesis runs, Figure 2 shows the mean and the standard variation (plotted as uncertainty bar) of the characteristic MPS parameters A 3 *, A 5 / A 3 , and ϕ 3 of the five individual runs synthesized either by micromixer (red) or batch synthesis (green). The specific amplitude A 3 * was a measure of the sensitivity of the MNP to give a dynamic magnetization response at a chosen excitation frequency f 0 per unit amount of iron, whereas the ratio A 5 / A 3 could be considered as a parameter to describe the shape of the harmonics spectrum [ 59 , 60 , 61 ]. Finally, phase ϕ 3 was related to the relaxation effects of the MNP and parametrized the lag of the MNP moments to follow the excitation field.…”
Section: Resultsmentioning
confidence: 99%